Correction to: Sugarcane Biomass as a Source of Biofuel for Internal Combustion Engines (Ethanol and Acetone-Butanol-Ethanol): A Review of Economic Challenges (Energies, (2022), 15, 22, (8644), 10.3390/en15228644) - Algayyim S.J.M.; Yusaf T.; Hamza N.H.; Wandel A.P.; Fattah I.M.R.; Laimon M.; Rahman S.M.A. (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
In the original publication [1], there was an error. The original article had incorrectly included the following article in the reference list: [84] ?[Vickers, N.J. Animal Communication: When I?m Calling You, Will You Answer Too? Curr. Biol.2017, 27, R713?R715]?. The intended reference for that statement should be [84] ?[Adsul, M.; Sandhu, S.K.; Sinhania, R.R.; Gupta, R.; Puri, S.K.; Mathur, A. Designing a cellulolytic enzyme cocktail for the efficient and economical conversion of lignocellulosic biomass to biofuels. Enzym. Microb. Technol.2020, 133, 109442]?. A correction has been made to 9. Economic Challenges, Paragraph 1 as follows: Biofuel production from sugarcane waste has some challenging factors. One obstacle is the high cost of the enzymatic hydrolysis process [46] that is used for biofuel production. In addition, another challenge is the low yield produced after fermentation. Carpio and Souza [83] evaluated biofuel production from second-generation bagasse using different market prices and bagasse allocation scenarios. The results analysis showed that the bagasse allocation to second generation ethanol increases with the reduction of its production costs. They also showed that second-generation ethanol production costs 0.30 USD/L. Several researchers have evaluated and analysed the traditional processing approaches used to reach the desired reduction in second-generation biofuel production costs. For example, using enzymatic cocktails for hydrolysis is one of the most critical steps in terms of processing cost reduction [84]. Prajapati et al. [85] produced high hydrolysis efficiency with 74.9% from cellulase and hemicellulose using novel technics. The authors state that the scientific conclusions are unaffected. This correction was approved by the Academic Editor. The original publication has also been updated. ? 2024 by the authors.